The Relationship of Anxiety Level with Osce Graduation on Students of The Faculty of Medicine YARSI University Class 2019 and 2020, and The Review According to Islamic Perspective - Muhammad Kholik Sanaba; Nunung Ainur Rahmah; Firman Arifandi (Junior Medical Journal, 2022)
Background: Anxiety is a condition that causes changes in a person's emotional atmosphere that can affect students' cognitive function when facing the Objective Structured Clinical Examination and affect student performance. According to the Qur'an, anxiety is explained by the phrase kha?f, which is a condition of unease about the future. This is caused by doubts in the heart or daiq so that hal?'a or anxiety occurs and results in feelings of suffering or hazn. The purpose of this study was to determine the relationship between anxiety levels with online and offline OSCE graduation, age, sex and identify the level of anxiety in YARSI University Faculty of Medicine Students Class of 2019 and 2020.Methods: This type of research is descriptive analytic with a cross sectional research design. The questionnaire was distributed via google form. This research was conducted on students of the Faculty of Medicine, YARSI University batch 2019 and 2020 with a total sample of 209 respondents. Data analysis using Kruskal Wallis test and Kolmogorov-Smirnov test.Results: Based on the results of statistical tests, there is no relationship between anxiety levels with sex, age, and online and offline OSCE graduation in YARSI University Faculty of Medicine Students Class of 2019 and 2020. The level of anxiety experienced by most students is a mild level of anxiety.Conclusion: There are no significant results between the level of anxiety with sex, age, and online and offline OSCE graduation.